The Effect of Factor Xa/Phospholipid Infusion on the Acute Phase Response in Baboons - Kruithof, Egbert K O; Agay, Diane; Mestries, Jean Claude; Gascon, Marie-Paule; Ythier, Arnaud (Thrombosis and Haemostasis, 1997)
Disseminated intravascular coagulation (DIC) is a frequent complication of septicemia or tissue injury and may be accompanied by elevations of interleukin-6, a mediator of the acute phase response. It is not known whether thrombin or fibrin deposition may directly induce an acute phase response. To study this, we employed a baboon model of in vivo thrombin generation, induced by the administration of purified bovine Factor Xa and phospholipid vesicles. Two Xa/phospholipid dosages were used, a low dosage (2 animals) leading to a rapid 49% decrease in fibrinogen and a high dosage (two injections at 5h interval; 3 animals) leading to complete fibrinogen depletion. Thereafter, fibrinogen levels increased in both treatment groups, reached a maximum of 2.52 ± 0.23 g/1 (mean ± SE, n = 5; p <0.01 with respect to basal levels) at day 2, and returned to normal by day seven. In five control (injection of 0.15% NaCl) baboons no significant changes of fibrinogen were observed (maximal values: 1.88 ± 0.12 g/1). Serum concentrations of C-reactive protein, an acute phase protein, increased from 3.7 ± 0.4 mg/1 to a maximum of 33.0 ± 7.3 at day one, which was five-fold higher (p <0.01) than in control animals at day one (6.2 ± 0.5 mg/1). Transient increases were observed within 6 h for interleukin-6 from basal values of 6.2 ± 1.7 ng/1 to peak plasma levels of 42.9 ±21.4 ng/1, a value threefold higher (p = 0.07) than in control animals (14.8 ± 4.0 ng/1).The preliminary results of this observational study suggest that factor Xa/phospholipid infusion is followed by an acute phase response, leading after one day to significant increases of fibrinogen and of C-reactive protein.